Nutritional knowledge of women with breast cancer and its relationship with nutritional status - Karin Sarkis Sedó; Carone Alves Lima; Priscila Carmelita Paiva Dias Carneiro; Larissa da Silva Albuquerque; Camila Oliveira de Araújo; Ádila da Silva Castro; Sara Maria Moreira Lima Verde (Universidade de Fortaleza, 2013)
Objective: To assess the nutritional knowledge of women with breast cancer on the dietdisease interface and its association with nutritional status. Methods: Observational, crosssectional and analytical study, conducted between June and September 2011, with 59 women diagnosed with breast cancer, undergoing chemotherapy or radiotherapy treatment, older than 19, who did not receive prior nutritional counseling. Vegetarian women or those whose treatment had been completed more than two years prior to the study were not included. The patients were treated at a cancer care reference center, in Fortaleza-CE. Clinical and socioeconomic data was collected through direct interview and searching in medical records. The assessment of nutritional knowledge (NK) was performed with the Nutrition Knowledge Scale, developed by the National Health Interview Survey Cancer Epidemiology, validated for Brazil, applied by a trained interviewer. Nutritional status was assessed through body mass index (BMI) and waist circumference. Data was analyzed statistically by SPSS 16.0. Results: Among 59 patients evaluated, 18 (30.5%) women had a limited knowledge of the diet-disease association. The mean BMI was 29 kg/m2 (± 4.4) and 47 (79.7%) women presented excessive weight (overweight or obesity). There was no correlation between nutritional knowledge and BMI (p = 0.64). Nutrition knowledge scores were similar among patients with overweight and normal weight (p = 0.89). Conclusion: Women in this study had a limited knowledge of the interface between diet and disease, were overweight, but there was no correlation between their nutritional knowledge and nutritional status.